2021
DOI: 10.1016/j.clnesp.2020.10.023
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of oncology survivors examining nutrition attitudes, problems and behaviours, and access to dietetic care throughout the cancer journey

Abstract: Background: Attitudes of cancer survivors to nutrition and nutrition care have rarely been captured. A better understanding of their needs based on a review of their experiences would give voice to this patient group (which has rarely been captured) and allow for better planning of nutritional care. Aims: To conduct a national survey to determine: (1) survivors' experience in relation to nutrition and diet-related problems, (2) perceived importance of the role of nutrition to cancer survivors, (3) the experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 44 publications
(30 reference statements)
4
83
1
5
Order By: Relevance
“…However, Moore et al (2017) identify factors at the level of the practitioner that prevent individualised care including: habitual practice; scepticism of alternative approaches; stereotypical attitudes and time constraints. In addition, Lloyd et al (2018) Most CRC survivors do not see a dietitian (Sullivan et al 2020); indeed, many prefer to receive information from a specialist nurse rather than a dietitian (Wright et al 2017). Enabling nurses to address the specific dietary information needs of CRC survivors is necessary to contribute to the delivery of high quality, person-centred oncology care.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…However, Moore et al (2017) identify factors at the level of the practitioner that prevent individualised care including: habitual practice; scepticism of alternative approaches; stereotypical attitudes and time constraints. In addition, Lloyd et al (2018) Most CRC survivors do not see a dietitian (Sullivan et al 2020); indeed, many prefer to receive information from a specialist nurse rather than a dietitian (Wright et al 2017). Enabling nurses to address the specific dietary information needs of CRC survivors is necessary to contribute to the delivery of high quality, person-centred oncology care.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…One of the most common questions of cancer patients and caregivers is "what should I eat or drink to improve my situation?" [58] This topic is very important but sometimes relatively neglected because of many time-consuming tasks associated with accurately prescribing chemotherapeutics and radiation therapy accurately and on time [58][59][60][61][62][63][64][65]. Fortunately, dietitians with oncology experience can provide tools and information to patients regarding food choices, eating behavior, and issues including poor oral intake and intermittent fasting when patients get chemotherapy and/or radiation [66][67][68].…”
Section: Review Of Strategies To Improve Eating Behaviors While Receiving Chemotherapy And/or Radiationmentioning
confidence: 99%
“…For a 70-kg man, this would be equivalent to expending 250 kcal/d through engagement in physical activities, including preparing meals and shopping. A recent survey of 1073 cancer survivors identified that nearly half of the participants experienced diet-related problems during their cancer treatments [96]. Nutrition-impact symptoms, including poor appetite and nausea, impede adequate intake and promote The result is a depleted state and a much longer recovery that may be incomplete from a skeletal muscle perspective.…”
Section: Prehabilitation Represents An Opportunity To Mitigate Sarcopenia and Frailtymentioning
confidence: 99%